Clinical Profile and Outcome of Acute Post-Streptococcal Glomerulonephritis in Children (Bangladesh Journal of Medical Science, 2011)
DOI: http://dx.doi.org/10.3329/bjms.v1i1.7848 Bangladesh Journal of Medical Science Vol.1(1) 1994 pp.22-27